Urban Sprawl Characteristics and Typologies in Romania - Bogdan Suditu; Anca Ginavar; Ana Muică; Crenguţa Iordăchescu; Amalia Vârdol; Bogdan Ghinea (Human Geographies: Journal of Studies and Research in Human Geography, 2010)
Urban sprawl limitation, moderate use of agricultural fields and ensuring the social mix are objectives of public policy of all European Community documents refering to urban and territorial planning, housing policies and territorial cohesion. In post-communist Romania the most obvious spatial effect of the liberalization of political and economical life is the multiplication of constructions from the periurban areas. The urban sprawl characteristics have an important role in the localities’ sustainable development and consequently in ensuring territorial cohesion.